Perception of Linguistic Ambiguity - Awwad, Mohammad (European Scientific Journal, ESJ, 2017)
A qualitative-quantitative study was conducted on students preparing for their Master’s degree in English, linguistic and literary branch, at the Lebanese University, the deanship, to investigate the participants’ perception of ambiguity in language. Ambiguity in language is considered a problematic issue since it hinders precise language processing. Ambiguity leads to a confusion of ideas in the reader’s mind, for the reader will struggle to decide on the precise meaning intended behind an utterance. This study presented a holistic view on EFL learners’ perception of ambiguity. Via three questionnaires, the subjects’ perception of ambiguity was tested on the recognition and production levels as well as sentential and textual levels. The results depicted that the subjects were unaware of ambiguous language, and at many times ambiguity hindered the subjects’ ability to process language precisely. The research threw at some strategies that aid in disambiguating ambiguous language on the production level, and deciphering ambiguity on the interpretation level. Implications and recommendations for teachers, students, and curriculum designers were offered in the light of the study’s findings.